2005
DOI: 10.1007/s10600-005-0144-5
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of Bovine Serum Albumin with D-[14C]-Glucose

Abstract: UDC 547.917 Certain parameters of the Maillard reaction between bovine serum albumin (BSA) and D-[ 14 C]-glucose were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…To evaluate the potential of aluminum oxide nanoparticles as a carrier for immunization, we first derivatized Al 2 O 3 by silanization to provide them with a terminal amine group. The amination percentage was 2%, which is similar to the theoretical proportion of primary amines for BSA (1.2%) 30 and higher than the theoretical proportion for ovalbumin (OVA) (<0.7%). On the other hand, the amine load was 32 μmol/g aluminum oxide, which is comparable to that of silanized Al 2 O 3 particles (16 μmol/g) that have been previously described.…”
Section: ■ Results and Discussionsupporting
confidence: 65%
“…To evaluate the potential of aluminum oxide nanoparticles as a carrier for immunization, we first derivatized Al 2 O 3 by silanization to provide them with a terminal amine group. The amination percentage was 2%, which is similar to the theoretical proportion of primary amines for BSA (1.2%) 30 and higher than the theoretical proportion for ovalbumin (OVA) (<0.7%). On the other hand, the amine load was 32 μmol/g aluminum oxide, which is comparable to that of silanized Al 2 O 3 particles (16 μmol/g) that have been previously described.…”
Section: ■ Results and Discussionsupporting
confidence: 65%
“…Often, the applied temperature determines which path of the reaction route prevails, complicating the comparison of results obtained at different temperatures . High temperatures, especially when applied to a system at high pH, have been found to be the most important factor enhancing the Maillard reaction. ,, The kinetics shown in Figure also indicate that the rate of BSA glucosylation decreases over time, causing a “tailing” of the kinetic curve. Martins and Van Boekel attributed this to the decrease in pH over time, due to the formation of acidic products, which consequently slows the Maillard reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The BSA−Glc mixtures were prepared by dissolving 2.5 mg/mL BSA and 25 mg/mL Glc in 0.05 M bicine buffer (#039K5437, Sigma) adjusted to pH 9.0. The high ratio of Glc to BSA was chosen to ensure a good degree of irreversible glucosylation . This is because sugars tend to react faster than amino compounds in the Maillard reaction, and they might caramelize, isomerize, fragment, or form diglucosylamines, whereas amino compounds might even be regenerated from the initial condensation product. , From the published literature, it was found that a common ratio for BSA:Glc mixtures is 1:5, which translates to a ratio of 12:1 for glucose per lysine residue.…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of glycated BSA Glycated BSA was prepared following the protocol of Kublashvili et al then purified following the protocol of Day (Day et al 1979;Kublashvili and Ugrekhelidze 2005). Because BSA is glycated at the same sites in vitro and in vivo, there was no need to isolate albumin from a live sample (Day et al 1979).…”
Section: Isolation and Purification Of Enterobactinmentioning
confidence: 99%